Influence of Visual Art Activities on Pupils’ Awareness of Insecurity and Civic Responsibility in Religion and National Values - Sule Muhammad; Nuraddeen Adamu Kanon-Haki (Universal Education Jurnal Teaching and Learning, 2025)
This study examined the influence of visual art activities on pupils’ awareness of insecurity and understanding of civic responsibility in the subject of Religion and National Values among basic schools in Gusau Metropolis, Zamfara State. Guided by Albert Bandura’s Social Learning Theory, the study adopted a quasi-experimental design involving 381 Basic Five pupils selected from six public schools (three experimental and three control). Pupils in the experimental group participated in structured visual art activities, including drawing, poster-making, and mural design, integrated into Religion and National Values lessons, while the control group received conventional instruction. Data collected through a validated questionnaire titled Visual Art and Civic Awareness Questionnaire (VACAQ) were analyzed using descriptive statistics and independent samples t-tests. Findings revealed that pupils exposed to visual art activities demonstrated significantly higher awareness of insecurity (M = 3.15, SD = 0.51) and greater understanding of civic responsibility (M = 2.96, SD = 0.58) than those in the control group (p < 0.05). The results confirm that visual art activities enhance pupils’ engagement, emotional reflection, and internalization of civic values. The study concludes that integrating art-based pedagogies into Religion and National Values instruction promotes peace education, moral development, and civic consciousness among pupils. It recommends curriculum enrichment, teacher training, and adequate resource provision to strengthen art-based learning for peacebuilding and civic education in basic schools.